Production of jet fuel range biofuels by catalytic transformation of triglycerides based oils. (15th January 2017) - Wu, Xiaoping; Jiang, Peiwen; Jin, Feng; Liu, Junxu; Zhang, Yiheng; Zhu, Lijuan; Xia, Tongyan; Shao, Kuanliang; Wang, Tiejun; Li, Quanxin
Graphical abstract: A proposed catalytic strategy for the production of cycloparaffinic and aromatic components in jet fuels from triglycerides based oils via the catalytic cracking of vegetable oils to light aromatics followed by the alkylation of light aromatics and the hydrogenation. Highlights: A proposed transformation of vegetable oils into bio-jet fuels was demonstrated. C6 –C9 aromatics were obtained by catalytic cracking of vegetable oil over HZSM-5 (80). Aromatic biofuel was achieved by the alkylation reactions using [bmim]Cl-2AlCl3 . Cycloparaffinic biofuel was produced by hydrogenation of aromatics over Pd/AC. Abstract: This work demonstrated that triglycerides based vegetable oils were directly converted into cycloparaffinic and aromatic components in jet fuel by a three-step process. This process involved the catalytic cracking of vegetable oils into light aromatics over the zeolite catalyst (HZSM-5(80)), followed by the aromatic alkylation of light aromatics using the ionic liquid of [bmim]Cl-2AlCl3 and the hydrogenation of aromatics over the Pd/AC catalyst. The production of C8 –C15 aromatics with an 86.2 wt% in the aromatic biofuel was achieved by the room temperature alkylation at 25 °C for 30 min. The carbon number distribution in the resulting biofuels was readily adjustable to the desired range by varying the reaction time. The aromatic and cycloparaffinic biofuels obtained basically meet the requirements of jet fuels based on the combustion heat, the H/C mol ratio and the average molecular formulation.